PERSEPSI MASYARAKAT TERHADAP AKUNTABILITAS DAN TRANSPARANSI PENGELOLAAN KEUANGAN DI DESA SUNGAI RAYA DALAM, KECAMATAN SUNGAI RAYA, KABUPATEN KUBU RAYA - Yasmin Alya Hanifadhila; Gita Desyana; Nella Yantiana (ITB AAS INDONESIA, 2024)
This research aims to know the perception of the village community regarding accountability and transparency of the management of the Income and Purchasing Budget of the Village in the village of Sungai Raya Dalam, Sungai Raya Prefecture, Kubu Raya District. The type of research used in this research is quantitative research descriptive, with data collection techniques using questionnaires. The population in this study is the village of Sungai Raya Dalam, Sungai Raya district, Kubu Raya district. Whereas the sample in this research is 32 (thirty-two) people of Riveside Village. The results of the research show that the perception of the community about the Government of Sungai Raya Dalam has been accountable and transponder in the management of the village's finances.